The Effect Of Profitabilty, Leverage, Audit Committee And Board Of Directors On Firm Value - Safarudin Riski Majid (JRAK: Journal of Accounting Research and Computerized Accounting, 2020)
This study aims to examine and analyze the effect of profitability, leverage, audit committee and board of directors on company value. The research method used is a quantitative method. The data used in this study are secondary data in the form of financial statements. The population in this study is LQ45 companies listed on the Indonesia Stock Exchange in 2015-2018. Samples were selected from the purposive sampling method and 28 samples were obtained based on several criteria. The analysis technique used in this study is multiple linear regression analysis. The analysis shows that profitability, leverage and audit committee influence the value of the company. While the board of directors has no effect on the value of the company. Simultaneously profitability, leverage, audit committee and board of directors affect the value of the company. The results also showed profitability, leverage, the audit committee and the board of directors were able to explain the dependent variable that is the value of the company by 95% and the rest was influenced by other variables. This research can be used by companies to increase the value of the company. Keywords : profitability, leverage, LQ45, firm value.